Cardamom extract alleviates tamoxifen-induced liver damage by suppressing inflammation and pyroptosis pathway - Wedad S. Sarawi; Hala A. Attia; Afraa Alzoubi; Nour Alanazi; Raeesa Mohammad; Rehab A. Ali (Scientific Reports)
Abstract Tamoxifen (TAM) is extensively used to manage estrogen receptor-positive breast cancer. Despite its effectiveness, its administration can negatively impact various organs, including the liver. This research focused on the effects of TAM on the pyroptotic pathway in the liver and evaluated the potential of cardamom extract (CRDE) to lessen hepatic damage of TAM in female rats. Rats received 45 mg/kg of TAM injections for 10 days, while the groups treated with CRDE received 12 ml/kg of CRDE for 20 days, commencing 10 days before TAM administration. TAM exposure resulted in apparent degenerations in hepatic tissue with inflammatory cell infiltration and loss of architectures. Serum levels of liver enzymes including alanine aminotransferase, aspartate aminotransferase and alkaline phosphatase were elevated, along with hepatic oxidative stress, as shown by increased lipid peroxidation with lower levels of reduced glutathione. TAM caused inflammation in the liver tissue as indicated by higher levels of tumor necrosis factor-α and interleukin-6 as well as increased expression of CD68; a phagocytic Kupffer’s cells marker. Additionally, the protein expression analysis revealed a high expression of pyroptotic markers including NLRP3-inflammasome, caspase-1, and gasdermin D. Conversely, CRDE treatment effectively neutralized the biochemical, histological, and protein expression alterations induced by TAM. In conclusion, CRDE demonstrated the potential to protect the liver from TAM-induced damage by regulating mechanisms involving oxidative damage, inflammation, and pyroptosis.